Алкілпохідні 7′-((3-меркапто-4-метил-1,2,4-триазол-5-іл)-метил)-5-метилксантину: синтез і властивості - Трофімова, Т. С.; Гоцуля, Андрій Сергійович; Trofimova, T. S.; Gotsulia, A. S. (My University, 2023)
Метою роботи був синтез S-алкілпохідних 7-((3-меркапто-4-метил-1,2,4-триазол-5-іл)метил)-3-метилксантину та попереднє встановлення фармакокінетичного профілю методами in silico. Вихідний 3-метилксантин було перетворено у 7-((3-меркапто-4-метил-1,2,4-триазол-5-іл)метил)-3-метилксантин. Одержаний тіол підлягав S-алкілуванню за участю галогеналканів. Будову та індивідуальність синтезованих сполук доведено за допомогою елементного аналізу, 1Н ЯМР-спектроскопії та хромато-мас-спектрометрії. Фармакокінетичні параметри речовин на відповідність критеріям лікоподібності було оцінено за допомогою on-line платформи SwissADME. Синтезовані речовини у in silico дослідженнях продемонстрували у своїй більшості здатність долати такі фільтри лікоподібності як Lipinski, Ghose, Veber, Egan, Muegge, що предиктивно визначає позитивний фармакокінетичний профіль досліджених сполук. Одержані значення таких дескрипторів як молекулярна рефракція та загальна площа полярних поверхонь молекул, а також показники ліпофільності лише посилюють висловлену думку. The aim of the study was to synthesize S-alkyl derivatives of 7-((3-mercapto-4-methyl-1,2,4-triazol- 5-yl)methyl)-3-methylxanthine and to determine the pharmacokinetic profile by in silico methods. The starting 3-methylxanthine was converted to 7-((3-mercapto-4-methyl-1,2,4-triazol-5-yl) methyl)-3-methylxanthine. The resulting thiol was subjected to S-alkylation with halogenalkanes. The structure and identity of the synthesized compounds were confirmed by elemental analysis, 1H NMR spectroscopy and chromatography-mass spectrometry. The pharmacokinetic parameters of the compounds and their compliance with the drug-like criteria were evaluated using the SwissADME on-line platform. The synthesized substances showed in the in silico studies were mostly able to overcome such drug-like filters as Lipinski, Gose, Weber, Egan, and Mugge, which predictively predetermines the positive pharmacokinetic profile of the studied compounds. The obtained values of such descriptors as molecular refraction and total area of polar surfaces of molecules, as well as lipophilicity indicators, only reinforce the above opinion.
Alkyl derivatives of 7′-((3-mercapto-4-methyl-1,2,4-triazol-5-yl)methyl)-3-methylxanthine: synthesis and properties
Гоцуля А. С. - https://orcid.org/0000-0001-9696-221Х
Keywords: 1,2,4-триазол; 3-метилксантин; синтез; властивості; докінг; 1,2,4-triazole; 3-methylxanthine; synthesis; properties; docking